A teoria do Impetus de Nicole Oresme e a possibilidade do Movimento diurno no Le livre du ciel et du monde - Campos, Alexandre (2008)
The objective of this dissertation is to analyse the possible connection between the Nicole Oresme s Impetus Theory and the arguments on the daytime earth s motion, present in Le Livre du Ciel et du Monde. To the end of this research it will be clear if Oresme used or not this concept to explain if this possible Movement began, of what it forms this it took place and his apparent uniform continuity. Charles V registers the analysis in the century XIV, when Oresme writes a commented translation of the Aristotelian treaty On the Heavens, to request of a king. His comments now they are simple interpretative explanations, it prays explanations followed by discussions in which he presents, through logical or theological arguments, other means to those present ones in the Aristotelian treaty. One of these means is the Daytime Movement of the Earth. In this work, also they will be presented and discussed: the origin and the conflicts that took place in the University of Paris, between the centuries XII and XIII up to the decree of Tempier in 1277; the concept of the Impetus, of Buridan, the discussions of Oresme on: the possibility of a produced and eternal World, the possibility of plural Worlds and the possibility of an incorporeal emptiness